Technology Addiction Survey: An Emerging Concern for Raising Awareness and Promotion of Healthy Use of Technology - Sharma, Manoj Kumar (Indian J Psychol Med, 2017)
BACKGROUND: Technology use has shown an impact of users’ lifestyle. The use has been attributed to psychosocial reasons. This usage manifests as excessive to addictive use of technology. There is a need to explore its addictive potential on large sample study as well as its association with psychosocial variables. It is one of its kind study on wider age group. The present work assessed the magnitude, burden, and sociodemographic correlates of technology addiction in an urban community. MATERIALS AND METHODS: A total of 2755 individuals (1392 males and 1363 females) in the age group of 18–65 years were approached for screening internet addiction and mobile overuse, using house-to-house survey methodology. RESULTS: The survey indicated the presence of addiction for 1.3% for internet (2% males and 0.6% females) and mobile phone overuse (4.1%–2.5% males and 1.5% females). It was more common among males. Significant differences were observed in relation to family status for internet and mobile phone use more commonly among single/nuclear families. Technology addictions were found to be more common among single families and lesser in nuclear and joint families. Mobile phone users had psychiatric distress in comparison to users with internet addiction. The study showed negative correlation of age, years of marriage, and numbers of family members with internet addiction and mobile overuse. CONCLUSIONS: It has implication for raising awareness about addictive potential of technology and its impact on one's lifestyle.